THE ISSUE OF THE CONSTRICTION OF CIVIL SOCIETY’S SPACE FOR ACTION AS A CONSEQUENCE OF THE EXPANSION OF THE AUTHORITY OF THE NATIONAL POLICE IN THE REVISION OF THE NATIONAL POLICE LAW - Sahwahita, Putri Nabila; Siregar, Nadya Zaharani; Ramadhani, Sinta (Zhata Institut, 2024)
As a democratic country, Indonesia should uphold the principles of civil liberties, including freedom of expression, assembly, and access to information. However, in practice, various human rights violations persist, with the Indonesian National Police (Polri) receiving the highest number of public complaints, including forced dispersals, arbitrary arrests, intimidation, and violence against civilians. Instead of implementing reforms to address these issues, the academic manuscript and the Second Amendment Bill to the Indonesian National Police Law (Police Bill) grant expanded powers that potentially threaten democracy. Therefore, this study aims to analyze and critique the impact of the Police Bill on the expansion of police authority, particularly concerning internet access and cyberspace, and propose a reformulation of the bill that prioritizes democratic values. This study employs a normative juridical research method using statutory and conceptual approaches. The findings highlight concerns over the police's authority to conduct wiretapping, block, and terminate access to cyberspace without clear oversight mechanisms, which risks restricting civic space, enabling abuses of power, and disrupting democratic processes. Thus, revisions to the academic manuscript and the substance of the Police Bill are necessary to emphasize fundamental improvements and strengthen oversight mechanisms.